Issues and ethics in the helping professions - Corey, Gerald (Brooks/Cole/Thomson Learning, 2003)
Designed for undergraduate and graduate students in the counseling and related fields, this text introduces ethics and shows its applications to all aspects of human services. The topics include multicultural perspectives, client rights, confidentiality, boundaries, professional competence, supervis